Mapping Missions: New Data for the Study of African History (Research Data Journal for the Humanities and Social Sciences, 2022)
The study of societal and institutional change has greatly benefited from a growing number of studies exploring sub-national variation in colonialism and its legacies. One vibrant stream in this literature focuses on the role of Christian missionaries in European empires. However, advances are often hampered by the quality and scarcity of available historical data. In this article, the authors introduce a new geospatial dataset of Catholic and Protestant mission stations in colonial Africa that offers a more complete picture than currently used data sources. The authors illustrate the greater coverage their data provides and demonstrate its utility by replicating the effect of missions on the expansion of formal education, one of the most established legacies of Christian missionaries.